At the Frontier of Particle Physics: Handbook of QCD: Boris Ioffe Festschrift ( Volume 2) - Shifman M (World Scientific, 2001)
This book consists of reviews covering all aspects of quantum chromodynamics as we know it today. The articles have been written by recognized experts in this field, in honour of the 75th birthday of Professor Boris Ioffe. Combining features of a handbook and a textbook, this is the most comprehensive source of information on the present status of QCD. It is intended for students as well as physicists - both theorists and experimentalists. Each review is self-contained and pedagogically structured, providing the general formulation of the problem, telling where it stands with respect to other issues and why it is interesting and important, presenting the history of the subject, qualitative insights and so on. The first part of the book is historical in nature. It includes, among other articles, Boris Ioffe's and Yuri Orlov's memoirs on high energy physics in the 1950's, a note by B.V. Geshkenbein on Ioffe's career in particle physics, and an essay on the discovery of asymptotic freedom written by David